No Association Between Human Immunodeficiency Virus Infections And Dementia: A Nationwide Cohort Study In Taiwan - Yang CC (Dove Medical Press, 2019)
Chuan-Chi Yang,1,2 Wu-Chien Chien,3–5 Chi-Hsiang Chung,3,4,6 Yia-Ping Liu,2,7–9 Chin-Bin Yeh,2 Kuang-Huei Chen,1 Szu-Nian Yang,1,9,10 Hsin-An Chang,2,11 Yu-Chen Kao,2,12 Wan-Chun Lu,2 Nian-Sheng Tzeng2,11 1Department of Psychiatry, Taoyuan Armed Forces General Hospital, Taoyuan, Taiwan, ROC; 2Department of Psychiatry, Tri-Service General Hospital, School of Medicine, National Defense Medical Center, Taipei, Taiwan, ROC; 3Department of Medical Research, Tri-Service General Hospital, National Defense Medical Center, Taipei, Taiwan, ROC; 4School of Public Health, National Defense Medical Center, Taipei, Taiwan, ROC; 5Graduate Institute of Life Sciences, National Defense Medical Center, Taipei, Taiwan, ROC; 6Taiwanese Injury Prevention and Safety Promotion Association, Taipei, Taiwan, ROC; 7Department of Psychiatry, Chen-Hsin General Hospital, Taipei, Taiwan, ROC; 8Institute of Physiology and Biophysics, National Defense Medical Center, Taipei, Taiwan, ROC; 9Graduate Institute of Medical Sciences, National Defense Medical Center, Taipei, Taiwan, ROC; 10Headquarters, Tri-Service General Hospital, Beitou Branch, National Defense Medical Center, Taipei, Taiwan, ROC; 11Student Counseling Center, National Defense Medical Center, Taipei, Taiwan, ROC; 12Department of Psychiatry, Tri-Service General Hospital, Song-Shan Branch, National Defense Medical Center, Taipei, Taiwan, ROCCorrespondence: Nian-Sheng TzengDepartment of Psychiatry, Tri-Service General Hospital, National Defense Medical Center, 325, Chung-Gung Road, Sec 2, Nei-Hu District 114, Taipei, Taiwan, ROCTel +886-2-87927299 ext 13674Email pierrens@mail.ndmctsgh.edu.twBackground: The associations between the human immunodeficiency virus (HIV) and dementias are as yet to be studied in Taiwan. The aim of this study is to clarify as to whether HIV infections are associated with the risk of dementia.Methods: A total of 1,261 HIV-infected patients and 3,783 controls (1:3) matched for age and sex were selected between January 1 and December 31, 2000 from Taiwan’s National Health Insurance Research Database (NHIRD). Fine and Gray’s survival analysis (competing with mortality) analyzed the risk of dementias during the 15-year follow up. The association between the highly active antiretroviral therapy (HAART) and dementia was analyzed by stratifying the HAART status among the HIV subjects.Results: During the follow-up period, 25 in the HIV group (N= 1,261) and 227 in the control group (N= 3,783) developed dementia (656.25 vs 913.15 per 100,000 person-years). Fine and Gray’s survival analysis revealed that the HIV patients were not associated with an increased risk of dementia, with the adjusted hazard ratio (HR) as 0.852 (95% confidence interval [CI]: 0.189–2.886, p=0.415) after adjusting for sex, age, comorbidities, geographical region, and the urbanization level of residence. There was no significant difference between the two groups of HIV-infected patients with or without HAART in the risk of dementia.Conclusion: This study found that HIV infections, either with or without HAART, were not associated with increased diagnoses of neurodegenerative dementias in patients older than 50 in Taiwan.Keywords: human immunodeficiency virus, highly active antiretroviral therapy, dementia, National Health Insurance Research Database, cohort study